Spectral Continiuty : (p, k) - Quasihyponormal and Totally p-(a,b) normal operators - R, Santhi; Kumar, D. Senthil (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
An operator T B(H) is said to be P- normal operators for . In this paper, we prove that continuity of the set theoretic functions spectrum, Weyl spectrum, Browder spectrum and essential surjectivity spectrum on the classes consisting of (p, k)- quasihyponormal operators and totally P- operators.